Cultural loneliness as attribute of a modern civilization system - Korkiya, Eka D. (Journal of the Belarusian State University. Sociology, 2020)
This article reveals the many-sided nature and content of the phenomenon of cultural loneliness as an important and contradictory spiritual state of a person and as a social phenomenon. The presented article systematizes the theoretical and methodological concepts of loneliness. The concept and essence of the phenomenon of «cultural loneliness» is revealed. In the course of the analysis, the ambiguity and complexity of this phenomenon were demonstrated and the specificity of the manifestation of cultural loneliness in various forms of social practice was shown.
Keywords: atomicity; general apathy; the deformed character of an individual; identity; cultural loneliness; cultural environment; massization; semantic space; sociality; civilization system